The place of oxycodone/naloxone in chronic pain management - Leppert, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2013)
Opioid analgesics are usually effective in the management of severe chronic pain. However, symptoms of opioid-induced bowel dysfunction (OIBD) are common during opioid therapy. Opioid-induced bowel dysfunction is often unsuccessfully managed due to limited effectiveness and numerous adverse effects of traditional laxatives. Newer treatment possibilities directed at the pathomechanism of OIBD comprise combined prolonged-release oxycodone with prolonged-release naloxone (oxycodone/naloxone) tablets. Oxycodone/naloxone provides effective analgesia with limited impact on bowel function as oxycodone displays high oral bioavailability and naloxone act as local antagonist on opioid receptors in the gastrointestinal tract due to nearly complete inactivation in the liver. Oxycodone/naloxone is administered to opioid-naive patients with severe pain and those unsuccessfully treated with weak opioids. Oxycodone/naloxone may be also administered to patients treated with strong opioids who experience intense symptoms of OIBD. Studies conducted to date indicate that oxycodone/naloxone is an important drug in chronic pain management, prevention and treatment of OIBD.